Rheological Properties of Cement Pastes with Multiwalled Carbon Nanotubes - Gintautas Skripkiunas; Ekaterina Karpova; Irmantas Barauskas; Joana Bendoraitiene; Grigory Yakovlev (Advances in Materials Science and Engineering)
The evaluation of rheological properties of cement systems is getting more relevant with growing interest to self-consolidating concrete (SCC), high-performance concrete (HPC) and ultrahigh-performance concrete (UHPC). The rheology models are a perspective tool to predict and manage the properties of cement systems in the fresh and hardened state. The current research is focused on the rheological test of cement systems modified by multiwalled carbon nanotubes (MWCNT) dispersion with and without polycarboxylate ether (PCE). The content of dispersion with 1% concentration of MWCNT in cement pastes varied from 0.125 to 0.5% by weight of cement. The dosage of PCE was taken as 0.6% by weight of cement. The cement pastes were prepared based on Portland cement without mineral additives. The rheological test was carried out at 5, 30, 60, and 120 min after mixing of cement paste. The rheological test established that modification of cement pastes by MWCNT dispersion in dosage 0.25% leads to the decrease of yield stress by 30.7% and increase of plastic viscosity by 29.6%. The combined modification by PCE and MWCNT dispersion shows the decrease in plastic viscosity of cement pastes by 9.90% in dosage of MWCNT equal to 0.5% by weight of cement, reduction of water demand by 20% for the same workability, and decrease of yield stress till 0 Pa. It gives the ability to obtain the self-compacting mixtures. The cement pastes with and without MWCNT dispersion revealed the shear-thinning behavior during 120 min after mixing. The modification of cement pastes by PCE with and without MWCNT dispersion showed the shear-thickening behavior which remains during 120 min after mixing.